Studies on the mechanism of general anesthesia - Pavel, Mahmud Arif; Petersen, E. Nicholas; Wang, Hao; Lerner, Richard A.; Hansen, Scott B. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Inhaled anesthetics are a chemically diverse collection of hydrophobic molecules that robustly activate TWIK-related K⁺ channels (TREK-1) and reversibly induce loss of consciousness. For 100 y, anesthetics were speculated to target cellular membranes, yet no plausible mechanism emerged to explain a membrane effect on ion channels. Here we show that inhaled anesthetics (chloroform and isoflurane) activate TREK-1 through disruption of phospholipase D2 (PLD2) localization to lipid rafts and subsequent production of signaling lipid phosphatidic acid (PA). Catalytically dead PLD2 robustly blocks anesthetic TREK-1 currents in whole-cell patch-clamp recordings. Localization of PLD2 renders the TRAAK channel sensitive, a channel that is otherwise anesthetic insensitive. General anesthetics, such as chloroform, isoflurane, diethyl ether, xenon, and propofol, disrupt lipid rafts and activate PLD2. In the whole brain of flies, anesthesia disrupts rafts and PLDnull flies resist anesthesia. Our results establish a membrane-mediated target of inhaled anesthesia and suggest PA helps set thresholds of anesthetic sensitivity in vivo.